2016
DOI: 10.3109/14756366.2016.1151013
|View full text |Cite
|
Sign up to set email alerts
|

Xylarinase: a novel clot busting enzyme from an endophytic fungusXylaria curta

Abstract: Xylarinase is a bi-functional fibrinolytic metalloprotease isolated from the culture filtrate of endophytic fungus Xylaria curta which is monomeric with a molecular mass of 33.76 kDa. The enzyme displayed both plasmin and tissue plasminogen activator like activity under in vitro conditions. It hydrolyses Aa and Bb chains of the fibrinogen. Optimal fibrinolytic activity of xylarinase is observed at 35 C, pH 8. Ca 2+ stimulated the fibrinolytic activity of xylarinase while Fe 2+ and Zn 2+ inhibited suggesting it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…(Gurumallesh et al 2019 ). Apart from these, many researchers have also explored the endophytic fungi for production of proteases for various purposes (Meshram et al 2016 ; Mandal and Banerjee 2019 ). Meshram and Saxena ( 2016 ) reported proteolytic and fibrinolytic activity in an endophytic fungal isolate Lasiodiplodia pseudotheobromae obtained from the stem of the Aegle marmelos , and proposed its potential use for dissolution of blood clots.…”
Section: Microbial Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Gurumallesh et al 2019 ). Apart from these, many researchers have also explored the endophytic fungi for production of proteases for various purposes (Meshram et al 2016 ; Mandal and Banerjee 2019 ). Meshram and Saxena ( 2016 ) reported proteolytic and fibrinolytic activity in an endophytic fungal isolate Lasiodiplodia pseudotheobromae obtained from the stem of the Aegle marmelos , and proposed its potential use for dissolution of blood clots.…”
Section: Microbial Proteasesmentioning
confidence: 99%
“…have the capability of producing alkaline proteases, but several fungi have also been reported to produce these enzymes (Sharma 2019 ). Meshram et al ( 2016 ) reported that a metalloprotease (with 8.0 pH optima) produced by endophytic fungus Xylaria curta possessed appreciable fibrinolytic properties, and thus has the potential of being used for therapeutic purposes. da Silva et al ( 2018 ) have carried out thermodynamic investigations on the serine alkaline protease produced by the fungus Aspergillus tamarii URM4634.…”
Section: Alkaline Proteasesmentioning
confidence: 99%
“…Other microorganisms such as algae, fungi, and fermented foods have also been used to obtain fibrinolytic enzymes by either using different fermentation methods or aqueous two phase systems (Nascimento et al, 2016;Meshram et al, 2017). Algae are sources for fibrinolytic enzymes that belong to proteases, metalloproteases, and tissue-type plasminogen activator (Choi et al, 2013;Kim et al, 2013;Moon et al, 2014;Kang et al, 2016;Min et al, 2016;Silva et al, 2018;de Barros et al, 2020) (Table 2); while fungi are important sources for fibrinolytic enzymes that belong to proteases, metalloproteases and metalloendopeptidase (Rovati et al, 2009;Choi et al, 2011;Kim et al, 2011;Liu et al, 2012;Palanivel et al, 2013;Ahmad et al, 2014;Liu et al, 2014;Kotb et al, 2015;Shukor et al, 2015;Meshram et al, 2016;Nascimento et al, 2016;Meshram et al, 2017;Liu et al, 2017;da Silva et al, 2019) (Table 3).…”
Section: Microorganisms As Sources Of Fibrinolytic Enzymesmentioning
confidence: 99%
“… Fungal-derived enzymes with fibrinolytic potential and their mechanism of action [ 5 , 31 , 66 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 ]. …”
Section: Microbes In Thrombolytic Therapymentioning
confidence: 99%
“…Figure 4. Fungal-derived enzymes with fibrinolytic potential and their mechanism of action [5,31,66,[101][102][103][104][105][106][107][108][109][110][111][112][113][114][115]…”
mentioning
confidence: 99%